Aporte de la educación ambiental en la teoría del reciclaje en los estudiantes del colegio San Juan Bautista de la Salle de la ciudad de Requena, Loreto, Perú 2021 - Angulo Gaviria, Gilcar Fidel Martin (2022)
The present research was carried out in Requena city, province of Requena, Department of Loreto, in order to identify what is the contribution of environmental education in the theory of recycling, in students of the public educational institution for minors - Colegio San Juan Bautista de Lasalle, in Requena city, Loreto, Peru, 2021. According to the results, there is an environmental aspect, according to the vigesimal scale, 26 students have a HIGH level of knowledge reaching the 50.98% of a total of 51 (100%), 16 people have a MEDIUM level with 31.37% and 9 people have a LOW level with 17.65%. Regarding knowledge of the forest, according to the vigesimal scale, in which we can affirm that of the people surveyed, 29 have a HIGH level of knowledge, reaching 56.86% of a total of 51 (100%), 11 people have a level MEDIUM with 21.57% and 11 people have a LOW level with 21.57% In knowledge of recycling, 27 students reach the HIGH category with 52.29% of the total, 14 students reach the MEDIUM category with 27.45% and 10 students reach the LOW category with 20.26%.